The mechanism-based approach of understanding run-in and steady state: A gross-slip fretting experiment to fathom tribocorrosion of total hip taper junctions. (March 2021) - Fischer, Alfons; Fullam, Spencer; Telouk, Philippe; Wimmer, Markus A.
Abstract: Fretting corrosion of biomedical taper junctions has raised concerns about adverse local tissue reactions. Particularly for CoCr29Mo6/TiAl6V4 couplings the exact mechanisms and interactions are not fully understood. Proteinaceous tribomaterial within such contact interface may act as boundary lubricant and hindering corrosive attack. In this context, it is an open question whether there is a difference between low-carbon and high-carbon CoCr29Mo6 alloys in contact with TiAl6V4. In order to study this, gross slip fretting tests were carried out in bovine calf serum (BCS) at 37 °C with both types of CoCr29Mo6 alloys against biomedical grade TiAl6V4. The appearance and depth of each wear scar were analyzed. In addition, the concentrations of metal ions within the BCS lubricant (representing the wear loss) and after cleaning of the metal samples within an enzyme-active detergent (representing the tribomaterial) were determined by means of ICP-MS. The wear behavior was characterized by microcutting and -ploughing (submechanisms of abrasion), by tribocorrosion (submechanism of tribochemical reactions), and by materials transfer (submechanism of adhesion). The ultra-mild wear rates of some ng/m and the average depth of the wear scars appeared unrelated. Thus, the tribomaterial had a protecting nature. The hard phases of the high-carbon CoCr29Mo6 metal matrix affected the run-in behavior, but not the material loss at steady state. Interestingly, TiAl6V4 always wore less than both CoCr29Mo6 alloys. Highlights: The wear mechanisms of low- and high-carbon CoCrMo alloys differ over the loading time. Run-in is faster for the high-carbon alloy for the additional action of hard phases protruding from the surface, leading to earlier generation of shelves on the Ti-side. The depths of the wear scars represent the generation of tribomaterial from constituents of both bodies and the lubricant and their reaction products. The depths of the wear scars are not characteristic for the wear loss in this ultra-mild wearing tribosystems.